From Isolation to Application: Utilising Phage‐Antibiotic Synergy in Murine Bacteremia Model to Combat Multidrug‐Resistant Enterococcus faecalis - Fatma Al‐zahraa A. Yehia; Galal Yahya; Eslam M. Elsayed; Javier Serrania; Anke Becker; Salwa E. Gomaa (Microbial Biotechnology)
ABSTRACT Enterococcus species, natural inhabitants of the human gut, have become major causes of life‐threatening bloodstream infections (BSIs) and the third most frequent cause of hospital‐acquired bacteremia. The rise of high‐level gentamicin resistance (HLGR) in enterococcal isolates complicates treatment and revives bacteriophage therapy. This study isolated and identified forty E. faecalis clinical isolates, with 30% exhibiting HLGR. The HLGR5 isolate, resistant to fosfomycin, vancomycin, and linezolid, was used to isolate the vB_EfaS_SZ1 phage from effluent water. This phage specifically lysed 42% of HLGR isolates. vB_EfaS_SZ1 demonstrated beneficial traits, including thermal stability, acid–base tolerance, a short latent period, and a large burst size. The phage genome comprises a 40,942 bp linear double‐stranded DNA with 65 open reading frames (ORFs). The genome closely resembled Enterococcus phages, classifying it within the Efquatrovirus genus. Phage‐antibiotic synergy was assessed using checkerboard assays and time‐killing analyses, revealing enhanced bacteriolytic activity of ampicillin and fosfomycin, with significant reductions in minimum inhibitory concentration values. In a mouse bacteremia model, phage‐antibiotic combinations significantly reduced E. faecalis liver burden compared to monotherapies. Histopathological analysis confirmed therapeutic synergy, showing reduced inflammation and improved hepatocyte regeneration. These findings underscore the potential of phage vB_EfaS_SZ1 as an adjunct to antibiotic therapy for resistant enterococcal bacteremia.